(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Equivalence is a central concept in translation studies, particularly in literary translation, where the transfer of cultural, emotional, and aesthetic values is as important as linguistic accuracy. This paper examines equivalence and translation strategies in literary translation, with a focus on achieving functional and dynamic equivalence. Drawing on a case study of selected literary texts, the paper explores how translators navigate challenges such as cultural references, idiomatic expressions, and stylistic nuances. By analyzing specific strategies, the study highlights the complexities of literary translation and the importance of balancing fidelity to the source text with the expectations of the target audience.